Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/trf.16555
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 antibody persistence in COVID‐19 convalescent plasma donors: Dependency on assay format and applicability to serosurveillance

Abstract: Background: Antibody response duration following severe acute respiratory syndrome coronavirus 2 infection tends to be variable and depends on severity of disease and method of detection. Study design and methods: COVID-19 convalescent plasma from 18 donors was collected longitudinally for a maximum of 63-129 days following resolution of symptoms. All the samples were initially screened by the Ortho total Ig test to confirm positivity and subsequently tested with seven additional direct sandwich or indirect bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 30 publications
4
45
0
Order By: Relevance
“…Although previous studies have shown that antibodies against the SARS-CoV-2 nucleocapsid wanes more quickly than those against the spike protein ( 22 , 23 ), 93% of persons who showed seroconversion at BD2 still had detectable nucleocapsid antibodies 6 months later. Direct antigen-sandwich format assays, such as the Roche anti-N assay used in our study, have been found to reliably detect antibodies in longitudinal samples ( 24 ). Of the few that seroreverted in this timeframe, the starting COI was low.…”
Section: Discussionmentioning
confidence: 86%
“…Although previous studies have shown that antibodies against the SARS-CoV-2 nucleocapsid wanes more quickly than those against the spike protein ( 22 , 23 ), 93% of persons who showed seroconversion at BD2 still had detectable nucleocapsid antibodies 6 months later. Direct antigen-sandwich format assays, such as the Roche anti-N assay used in our study, have been found to reliably detect antibodies in longitudinal samples ( 24 ). Of the few that seroreverted in this timeframe, the starting COI was low.…”
Section: Discussionmentioning
confidence: 86%
“…These controversies could be partly due to different ELISAs that were applied. Unlike traditional indirect ELISAs (antigen-antibody-antibody), antigen sandwich assay (antigen-antibody-antigen) uses a labeled virus antigen instead of labeled secondary anti-human antibody for detection, so that each anti-SARS-CoV-2 antibody bridges two recombinant antigens of the virus that affect the sensitivity of the test ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The samples were first tested using an anti-N SARS-CoV-2 IgG chemiluminescence microparticle assay (CIMA, Abbott Park, IL, USA), and then the samples with enough volume were retested using the Abbott anti-S SARS-CoV-2 IgG CIMA. These are high specificity assays whose reactivity consistently wanes during convalescence [1,13,14] and presents small measurement error (see Supplemental Appendix).…”
Section: Methodsmentioning
confidence: 99%